The role of end-of-life communication in contributing to palliative-oriented care at the end-of-life in nursing home. (2nd January 2022) - Gonella, Silvia; Basso, Ines; Dimonte, Valerio; Giulio, Paola Di
Abstract : Background: Clear communication about a person's poor prognosis and limited treatment choices improves the quality of end-of-life care. Aims: To investigate how end-of-life communication may contribute to palliative-oriented care at the end-of-life in nursing homes according to both families' and nurses' perspective. Secondly, to identify the contextual factors internal to the nursing home that may influence the timing and quality of communication. Thirdly, to confirm the foundations for a first theory of end-of-life communication. Method: This study is a descriptive two-tailed embedded multiple-case study. A secondary analysis of 23 family carer-nurse paired interviews was performed. Findings: Several contextual factors influenced the timing and quality of communication that, in turn, impacted end-of-life care by promoting family understanding, fostering shared decision-making between healthcare professionals and resident/family carers, and improving the knowledge of residents' and family carers' preferences (ie drivers of transition towards palliative-oriented care). Family carers' preferences had the strongest influence in guiding the care approach, while residents' preferences were poorly known and had a limited impact on the end-of-life care goal. Complex and dynamic interactions within and between drivers and contextual factors emerged, providing preliminary evidence for a first end-of-life communication theory. Conclusion: Findings suggest the need to promote a familiar atmosphere and quality relationships, and improve the knowledge of a resident's preferences to ensure that end-of-life care is consistent with their desires.